“Divorcio”: la autobiografía de Na Hye-seok - Park, Morgan Mok-Won (El Colegio de México, 2023)
In the 1920s and 1930s when Korea was under Japanese colonial rule, the ideology of chastity was imposed on women to ensure its lineage. In contrast, men were free to divorce and restart their lives with their concubines. Without the right to custody of children or division of property, divorced women were stigmatized and forced into poverty. Na Hye-seok (1896–1948), a “new woman” and a pioneer, with a modern education, denounced this social injustice against women in her autobiography I-hon-go-baeg-jang 이혼 고백장 [Confession of Divorce] (1934), in which she recounted her personal experiences. The first Spanish translation of the chapter “Divorce” is presented here.